Integrasi Legislasi Syariah dalam Sistem Hukum Modern: Tantangan dan Peluang di Era Digital - Syahrul; Muhammad Audy Andy; Rifyan Zahir; Kurniati (Aksioreligia, 2025)
The integration of Sharia legislation into the modern legal system is becoming increasingly relevant in the digital era. Advances in technology and globalization demand the harmonization of Islamic law with contemporary regulations to address social, economic, and political challenges. This study aims to analyze the opportunities and challenges of integrating Sharia law into modern legal systems, particularly in the context of digitalization. The research employs a qualitative approach with a descriptive-analytical method. Data is obtained through a literature review encompassing Islamic legal literature, statutory regulations, and academic studies on digital law and technology. The analysis is conducted using comparative and interpretative methods to examine the application of Sharia law in various countries. The findings indicate that despite challenges such as differences in legal concepts, social resistance, and digital infrastructure limitations, the digital era also presents significant opportunities for Sharia legislation. The use of technologies such as blockchain, artificial intelligence, and smart contracts can enhance transparency and effectiveness in applying Sharia law. With adaptive regulatory strategies and collaboration among scholars, academics, and technology experts, the integration of Sharia legislation into modern legal systems can be achieved in a more inclusive and applicable manner.